Avaliação da atividade antinociceptiva do extrato e do alcaloide s-(+)-dicentrina extraído de frutos de Ocotea puberula (Lauraceae) - Montrucchio, Deise Prehs (2012)
Ocotea puberula (Lauraceae) is a brazilian native tree, known in the South regions as canela guaicá or canela amarela. Its phytochemical composition includes several alkaloids of aporphinic type, some of them with biological activities already reported. Fruits collected in Curitiba, state of Paraná, were submitted to extraction and fractioning processes, allowing the isolation of an alkaloid identified as dicentrine, present as the majoritarian substance. In the present work we investigated the antinociceptive potential of the organic fractions obtained from O. puberula fruits extract and dicentrine (DCTN) isolated from the chloroform fraction (CF). Both CF and DCTN, given by oral route, were able to reduce the nociception induced by formalin and acetic acid with similar ID50, suggesting that the CF effect is due to the presence of DCTN. Hexanic (HF) or ethyl acetate (EAF) fractions had no antinociceptive effect. DCTN also presented antinociceptive effects in chronic models such as inflammatory (induced by intraplantar injection of Freund s complete adjuvant) and neuropathic (induced by partial sciatic nerve ligation), being able to reduce mechanical and cold hypersensitivity,with no changes in the response to heat. When evaluated against the thermo-receptors activation, DCTN administered either systemically (by oral route) or locally (by intraplantar route) reduced the nociception induced by cinnamaldehyde, a TRPA1 activator, but did not alter the response induced by capsaicin, a TRPV1 activator. The antinociceptive effect of DCTN was not affected by the pretreatment with antagonists of opioid, adrenergic or cannabinoid receptors, and neither by the pretreatment with an inhibitor of serotonin synthesis, suggesting that these descending mechanisms of pain control are not involved in the DCTN mechanism of action. On the other hand, DCTN was able to prevent the hypersensitivity induced by cAMP/PKA pathway activators, forskolin and PGE2, and it also reduced PKA activation, demonstrated by western blotting analysis, suggesting that DCTN may act by interaction with this signaling pathway. On the other hand, DCTN presented few or none action on the hypersensitivity induced by bradikinin or PMA, respectively, suggesting that the PLC/PKC pathway is not involved in DCTN antinociceptive action. Additionally, DCTN did not cause any sedative effect, neither alterations on motor activity or body temperature, and although daily treatment caused a slight increase in liver relative weight, alterations on AST, ALT or γ-GT levels were not observed. Together, these results demonstrate that DCTN has an important antinociceptive effect in acute and chronic models of pain, mainly of inflammatory origin, and its mechanism of action seems to involve an interaction with TRPA1 channels and the cAMP/PKA signaling pathway. In this way, DCTN may be considered a potential candidate to further pre-clinical and even clinical investigations for development of analgesic drugs.